The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1002/jmv.1890190407
|View full text |Cite
|
Sign up to set email alerts
|

The association of rhinoviruses with lower respiratory tract disease in hospitalized patients

Abstract: An analysis of 32 hospitalized infants and children from whom rhinoviruses were isolated in our diagnostic laboratories in 1982-83 suggests that these agents are associated with lower respiratory tract disease with focal findings in susceptible patients. In 23 cases, an acute lower respiratory disease was the cause for admission, while nine patients were cultured after new respiratory symptoms developed during hospitalization. Presenting signs and symptoms included cough (23), fever (19), rhinorrhea (19), resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 20 publications
1
38
1
Order By: Relevance
“…In earlier studies, group A RVs were also detected less frequently than group B RVs (1,2,24,26,32). Although at present, a higher number of group B RVs is known than group A RVs, analysis of epidemiological data indicated that group B RVs produced more than twice as many clinical infections per serotype as group A RVs did.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In earlier studies, group A RVs were also detected less frequently than group B RVs (1,2,24,26,32). Although at present, a higher number of group B RVs is known than group A RVs, analysis of epidemiological data indicated that group B RVs produced more than twice as many clinical infections per serotype as group A RVs did.…”
Section: Discussionmentioning
confidence: 75%
“…However, they may also be associated with more-severe lower respiratory tract infections in children, in the elderly (23,24,30,33), and in immunocompromised patients (14,39,48,49). RVs have been isolated from cases of cystic fibrosis (44), otitis media (3), sinusitis (37), and exacerbations of chronic bronchitis and asthma (12,21,22,34).…”
mentioning
confidence: 99%
“…Despite a careful search for rhinovirus and enterovirus isolation data, no references were found in the literature to the isolation of either EV68 or HRV87 from clinical specimens after their first appearance and characterization. Serotyping of rhinovirus isolates is laborious and has been carried out in only a few studies (6,14,16,18). However, the typing of enteroviruses has been widespread and has resulted in lengthy reports of clinical enterovirus findings.…”
Section: Discussionmentioning
confidence: 99%
“…HRVs have been found to replicate effectively in lower airways and have been recovered from bronchoalveolar lavage fluids and bronchial biopsy samples (13,19,22,27,28). These viruses have been implicated as causes of asthma exacerbations (9,25) and severe respiratory tract illnesses in children, the immunosuppressed, and the elderly (3,5,7,21,29).…”
mentioning
confidence: 99%